The Skin-Lightening Power of Tirbanibulin 1% Ointment - Federica Li Pomi; Andrea d’Aloja; Michelangelo Rottura; Mario Vaccaro; Francesco Borgia (Dermatology and Therapy)
Abstract Background Tirbanibulin 1% ointment has been licensed to treat non-hyperkeratotic actinic keratosis (AK) on the face and scalp in adults. Recent evidence suggests that, besides the antineoplastic effect, tirbanibulin may also confer substantial cosmetic benefits to patients. Methods We report a single-center retrospective study of patients affected by solar lentigines (SLs) and AKs in the context of field cancerization treated with tirbanibulin 1% ointment. Results Among 42 patients, 35% (n = 15) experienced complete clearance of SLs, while partial clearance was observed in 50% (n = 21) of patients. Regarding AKs, complete and partial clearance were observed in 52% (n = 22) and 40% (n = 17) of patients, respectively. Major study limitations are the small sample size and the absence of a control group. Conclusions Our results suggest that tirbanibulin 1% ointment may offer the dual benefit of treating AKs while simultaneously lightening aesthetically bothersome and difficult-to-treat lesions like SLs with just 5 days of application.